Anti-tumor activity of the combination of bendamustine with vorinostat in diffuse large B-cell lymphoma cells. Issue 3 (3rd March 2016) - Fernández-Rodríguez, Concepción; Salar, Antonio; Navarro, Alfons; Gimeno, Eva; Pairet, Silvia; Camacho, Laura; Ferraro, Mariana; Serrano, Sergi; Besses, Carles; Bellosillo, Beatriz; Sanchez-Gonzalez, Blanca
Abstract : Current standard-of-care therapy for diffuse large B-cell lymphoma (DLBCL) results in up to 40% of patients who either relapse or develop refractory disease. In this setting, further therapeutic improvements are needed. This study analyzed the in vitro effects of the combination of bendamustine with the histone deacetylase inhibitor vorinostat in DLBCL cells. This combination enhanced histone acetylation and double strand DNA breaks resulting in an additive to synergistic cytotoxic effect in both ABC- and GCB-type DLBCL cells, independently of their TP53 mutational status. These results support the rationale for considering bendamustine and vorinostat combination as a novel approach in DLBCL treatment.